Fig. 13 in Hyoliths and small shelly fossils from the Lower Cambrian of North-East Greenland - Malinky, John M.; Skovsted, Christian B. (Zenodo, 2004)
Fig. 13. Coleolus sp. A. MGUH 27119, from GGU sample 314933, lateral view. B. MGUH 27120, from GGU sample 314835; B1–B3, lateral views; B4, cross−section. C. MGUH 3527 from the collections of C. Poulsen, lateral view. Scale bars 1 mm. Published as part of Malinky, John M. & Skovsted, Christian B., 2004, Hyoliths and small shelly fossils from the Lower Cambrian of North-East Greenland, pp. 551-578 in Acta Palaeontologica Polonica 49 (4) on page 571, DOI: 10.5281/zenodo.13522197